(untitled) (Journal of the College of Basic Education, 2022)
This study aimed to measure the impact of using computer technology in science education: a field study from the point of view of science teachers for the secondary and preparatory stages in the Damascus Education Directorate. This questionnaire consists of (20) paragraphs. The descriptive survey method was used in the study, by distributing the questionnaires to all members of the study community from science teachers to the secondary and preparatory stages in the Damascus Education Directorate and surveying them during the academic year 2021-2022. The results of the study showed the following: The degree of impact of using computer technology in teaching science from the point of view of science teachers in the Damascus Education Directorate was medium, and also showed that there were statistically significant differences at the significance level (α≤ 0.05) in the degree of computer use in teaching Science: From the point of view of science teachers in the Damascus Education Directorate, it is attributed to the variable: the academic stage. The study recommended holding special sessions for students and teachers to employ and use all available tools for the educational process.